ANALISIS SWOT SEBAGAI STRATEGI PERUSAHAAN DALAM MEMENANGKAN PERSAINGAN BISNIS - Dwi Sulistiani (lp2m-uin malang, 2014)
Oleh: Dwi Sulistiani UIN Maulana Malik Ibrahim Malang Email: tiaraakbar2006@yahoo.com Abstract In the current information era, the level of competition is getting tough , so we need a strategy to win the competition . The success of a strategy for implementation would have been very dependent on the accuracy of the reading strategies of internal conditions, environmental changes and the level of competition . This is used to read an analysis of internal strengths and weaknesses, and the opportunities and threats from the external environment . SWOT analysis is one option to be able to assist in making an effective strategy to win the competition . SWOT analysis is very simple and easy to use but able to give a detailed picture of the internal and external environmental conditions . This analysis is widely used for the preparation of strategic business planning that is aimed to develop a long term strategy so that the direction and objectives can be achieved and targeted so that a decision can be taken . The purpose of this paper is to provide an overview of how the need for an analytical tool in understanding the internal condition of both the weaknesses and strengths as well as addressing the external environment in the form of threats and opportunities to take a strategic decision in the face of competition in the global era. Keywords : Competition , Internal and External Conditions , Strategic Planning , SWOT